Sliding wear behavior of PVD CrN and TiN coated austempered ductile iron - Colombo, Diego Alejandro (2014)
This work studies the sliding wear behavior of PVD coated austempered ductile iron samples. The effects of the substrate surface finishing method (grinding and polishing) and coating material (CrN and TiN) on the wear behavior are evaluated. Coatings were applied in an industrial reactor. Deposition times were adjusted to obtain similar film thicknesses in both coating materials. Wear tests under dry sliding conditions were carried out with a pin–on–disc tribometer (ASTM G99). The steady–state friction coefficient and wear rate were calculated for each sample variant. The wear track of the discs was examined by using optical microscopy and stylus profilometry. The results obtained indicate that the uncoated and TiN coated samples show steady–state friction coefficients close to 0.8, while the CrN coated samples show steady–state values close to 0.4. The sliding wear tests do not produce the fracture and/or delamination of the films in any case. The specific wear rate of the CrN and TiN coated samples is close to zero, while that of the uncoated samples is higher. The wear rate of the uncoated samples is slightly higher for the ground ones. The specific wear rate of the pins (AISI 52100 bearing balls) is higher than that of the discs in all the cases. The wear rate of the pins tested against uncoated samples is higher for the ground ones. The wear rate of the pins tested against coated samples is higher for the polished and TiN coated ones.